Functional properties of pineapple plant stem for enhanced glucose recovery in amino acids production - Chu, Pei Hsia; Jenol, Mohd Azwan; Phang, Lai Yee; Syed Muhammad, Sharifah Kharidah; Abd Aziz, Suraini (MDPI AG, 2022)
Pineapples generate large amounts of agricultural wastes during their production. To reduce environmental impacts due to poor handling of these wastes, the underutilised pineapple plant stem (PPS), which has a high starch content, can be explored for its sugar recovery. To achieve this, gelatinisation is a key process in increasing enzymes’ susceptibility. Therefore, this study aimed to enhance glucose recovery from PPS by studying the effects of gelatinisation temperature and time on its functional properties. Afterwards, the fermentable sugar obtained was used for amino acids production by Bacillus subtilis ATCC 6051. PPS has a high gelatinisation temperature (To = 111 °C; Tp = 116 °C; Tc = 161 °C) and enthalpy (ΔH = 263.58 J/g). Both temperature and time showed significant effects on its functional properties, affecting enzymatic hydrolysis. Gelatinisation temperature of 100 °C at 15 min resulted in maximum glucose recovery of 56.81 g/L (0.81 g/g hydrolysis yield) with a 3.53-fold increment over the control. Subsequently, utilisation of PPS hydrolysate in the fermentation by B. subtilis ATCC 6051 resulted in 23.53 mg/mL amino acids being produced with productivity of 0.49 g/L/h. This opens up new opportunities for the applications of PPS as well as B. subtilis ATCC 6051 in the amino acids industry.